Pengaruh Pajak Hotel, Pajak Restoran, Pajak Reklame, dan Pajak Penerangan Jalan Terhadap Pendapatan Asli Daerah - Tang, Sefnat Aristarkus; Leto, Chrisyantus (Peneliti.net, 2025)
Local Original Income (PAD) is all local regional revenues sourced from regional taxes, regional levies, results of management of separated regional assets, and other legitimate PAD. This study aims to determine the effect of hotel tax (PH), restaurant tax (PR), advertising tax (PRl), and street lighting tax (PPJ) on the local original income (PAD) of Alor Regency in 2019-2023. Data collection using observation, interviews, and documentation studies. While data analysis uses descriptive statistics, classical assumption tests, and multiple linear regression. Hypothesis testing uses partial tests and simultaneous tests. The results of the study indicate that partial hotel tax has a positive and significant effect on local original income as indicated by a significant t-test value of 0.039; restaurant tax has a positive and significant effect on local original income as indicated by a significant t-test value of 0.000; advertising tax has a positive and significant effect on local original income as indicated by a significant t-test value of 0.048; street lighting tax has a positive and significant effect on local revenue as indicated by the significant value of the t-test of 0.031, and simultaneously hotel tax, restaurant tax, advertising tax, and street lighting tax have a positive and significant effect on local revenue as indicated by the significant value of the F-test of 0.000.